2009
DOI: 10.1371/journal.pone.0007743
|View full text |Cite
|
Sign up to set email alerts
|

An Integrated Analysis of Molecular Acclimation to High Light in the Marine Diatom Phaeodactylum tricornutum

Abstract: Photosynthetic diatoms are exposed to rapid and unpredictable changes in irradiance and spectral quality, and must be able to acclimate their light harvesting systems to varying light conditions. Molecular mechanisms behind light acclimation in diatoms are largely unknown. We set out to investigate the mechanisms of high light acclimation in Phaeodactylum tricornutum using an integrated approach involving global transcriptional profiling, metabolite profiling and variable fluorescence technique. Algae cultures… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

32
260
6
2

Year Published

2010
2010
2024
2024

Publication Types

Select...
8
2

Relationship

0
10

Authors

Journals

citations
Cited by 239 publications
(312 citation statements)
references
References 67 publications
32
260
6
2
Order By: Relevance
“…Their accumulation upon light stress has been associated with enhanced photoprotection in the green freshwater alga Chlamydomonas reinhardtii (15). A similar role was recently proposed for diatom orthologs that are upregulated in high light (16)(17)(18). On the other hand, gene expression analyses revealed that one of the four LHCX genes of P. tricornutum (LHCX1) is not light-stress responsive ( Fig.…”
Section: Lhcx1 Is Required For Light Responses In Both Stress and Nonsupporting
confidence: 62%
“…Their accumulation upon light stress has been associated with enhanced photoprotection in the green freshwater alga Chlamydomonas reinhardtii (15). A similar role was recently proposed for diatom orthologs that are upregulated in high light (16)(17)(18). On the other hand, gene expression analyses revealed that one of the four LHCX genes of P. tricornutum (LHCX1) is not light-stress responsive ( Fig.…”
Section: Lhcx1 Is Required For Light Responses In Both Stress and Nonsupporting
confidence: 62%
“…The comparison of Pt-DPH absorption spectra with the action spectra for gene expression showed that maximal induction of selected FR-responsive genes occurs at wavebands specific to the Pfr form. Analyses of these genes in transcriptome data sets from P. tricornutum cells exposed to other wavebands (blue, green, red, and white) (Nymark et al, 2009;Chauton et al, 2013;Valle et al, 2014) showed either no expression changes or opposite changes compared with those induced by FR. The loss of responsiveness of Class 1 genes in knockout cells further demonstrated the involvement of DPH in FR light signaling (Figure 3).…”
Section: Discussion Diatom Phytochrome Mediates Fr Light Signalingmentioning
confidence: 97%
“…In P. patens, the upregulation by zeaxanthin of the LHCSR-dependent NPQ component is far stronger than the complementary PSBS-dependent component, leading to a strong control of zeaxanthin over NPQ to a level unprecedented in green algae and plants (Figures 2B and 2C). High zeaxanthin dependence of NPQ amplitude was reported in diatoms (Coesel et al, 2008;Nymark et al, 2009;Bailleul et al, 2010). While NPQ is decreased in a LHCSR knockdown genotype (lhcx1), clear evidence that LHCSR is the only agent for NPQ is lacking in these algae (Lavaud et al, 2012).…”
Section: Discussionmentioning
confidence: 99%